Botanical origin of monovarietal dark honeys (from heather, holm oak, pyrenean oak and sweet chestnut) based on their chromatic characters and amino acid profiles (European Food Research and Technology, 2006)
An early optimisation of the o-phthaldialdehyde (OPA) method for the HPLC-ﬂuorimetric analysis of amino acids in honey and bee-pollen made feasible the quantiﬁ- cation of 23, which included ﬁve infrequently searched for. Forty samples of monovarietal dark honeys, from four botanical origins, were analysed for their amino acids’ proﬁle (which included proline) and their colour. In order to test for their botanical classiﬁcation stepwise linear discriminant analysis was applied to a number of variables made from a selection of analytical results and simple mathematical functions of them. This allowed, ﬁrstly, distinguishing honeys from these four botanical sources with 85.0% cross-validated grouped cases correctly classiﬁed. A second application was made for the group of honeydew honeys—a matter of particular interest since no chemical or microscopic method exists for the honeys from holm oak and oak. Ninety-ﬁve percent of the cross-validated samples were correctly classiﬁed, only one sample was misclassiﬁed.